TRACTOR AND VEHICLE STABILITY (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The stability of mobile power units (MPU) is characterized by their ability to operate on longitudinal and transverse gradients without overturning and sliding. In this regard, a distinction is made between longitudinal and transverse stability. Rolling of a wheeled tractor standing on an uphill slope is prevented by braking force Ptand rolling resistance moment, Various ways of increasing not only longitudinal stability, but also controllability of MPU are used, such as reducing the vertical coordinate of the center of gravity ts (in the case of low-clearance tractors), attaching weights to the front of the tractor, increasing the longitudinal base of machines, and to increase af - drive all wheels from the transmission.